Deciphering the role of reactive oxygen species in idiopathic asthenozoospermia - Wang, Zilong; Li, Dandan; Zhou, Guoyi; Xu, Zhen; Wang, Xinkun; Tan, Senbao; Li, Zhenghao; Li, Xiaoli; Song, Changze; Yuan, Song (Frontiers in Endocrinology, 2025)
Asthenozoospermia is a severe condition characterized by abnormal sperm motility, contributing to 50% of male infertility cases. Idiopathic asthenozoospermia refers to a form of this condition with no identifiable causes through routine clinical examinations, potentially linked to apoptosis and oxidative stress induced by excessive reactive oxygen species (ROS). At low concentrations, ROS positively influence physiological processes, including sperm mature and motility. However, elevated ROS levels can harm human spermatozoa through oxidative stress, primarily due to the absence of effective DNA damage repair mechanisms and inadequate antioxidant defenses. In this review, we summarize the physiological and pathophysiological roles, endogenous and exogenous sources, and therapeutic strategies related to ROS in idiopathic asthenozoospermia. Ultimately, maintaining a proper balance between ROS concentrations and antioxidants is crucial for ensuring male reproductive health.